1992
DOI: 10.1148/radiology.185.3.1438772
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: spinal MR imaging in patients with untreated newly diagnosed disease.

Abstract: Spinal magnetic resonance (MR) imaging was performed in 29 patients with newly diagnosed, untreated multiple myeloma. Nineteen (66%) patients were asymptomatic. Sagittal pre- and postcontrast T1-weighted spin-echo images and gradient-recalled-echo images of the thoracic and lumbosacral spine were obtained. Marrow involvement was identified in 20 (69%) patients. There were three MR patterns: focal lesions in nine patients (31%), diffuse involvement in seven (24%), and an inhomogeneous pattern of tiny lesions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
90
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(102 citation statements)
references
References 0 publications
8
90
0
2
Order By: Relevance
“…Thus, MRI of the spine and pelvis was more sensitive and specific than PET-CT, particularly among patients lacking a focal MR bone marrow pattern. On the basis of these results, which resemble those of previously published studies, 22,24 and in the light of the adverse prognostic relevance of an abnormal diffuse MR pattern of the spine, 18 it can be concluded that MRI still remains the gold standard technique for the detection of bone marrow involvement of the spine and pelvis.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Thus, MRI of the spine and pelvis was more sensitive and specific than PET-CT, particularly among patients lacking a focal MR bone marrow pattern. On the basis of these results, which resemble those of previously published studies, 22,24 and in the light of the adverse prognostic relevance of an abnormal diffuse MR pattern of the spine, 18 it can be concluded that MRI still remains the gold standard technique for the detection of bone marrow involvement of the spine and pelvis.…”
supporting
confidence: 86%
“…They independently evaluated the bone marrow infiltration and, on the basis of previously reported criteria, identified the following patterns of bone marrow involvement: normal, focal and diffuse. 18 In the case of focal pattern, the exact number and site of lesions were reported. WBXR survey included plain radiographs of the skull, spine, pelvis, ribs, femora and humeri.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infiltration of the bone marrow by myeloma has been described previously as broad categories of focal, patchy/variegated, or diffuse infiltration. [16][17][18][19][20][21][22] The current study describes a semiquantitative way to assess bone marrow infiltration by MRI that may be more reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, in the most recent studies, the pathological FDG uptake is characterized by SUVmax (with a cut-off value 2.5 and/ or 4.2) and only the PET positive and PET negative groups are created; therefore, we also analysed the data in the same way in our study. Several studies have shown that an MRI is more sensitive than a whole-body X-ray for the detection of bone involvement in MM [21][22][23] . In 2013, a meta-analysis confirmed the superiority of MRI over wholebody Xray, mainly in the axial skeleton [3,24] .…”
mentioning
confidence: 99%